الرضا الوظيفي كمتغير وسيط بين الرأس المال الفكري وتطبيق إدارة الجودة الشاملة: دراسة حالة مركب الحجار - بلبخاري, سامي; طحطوح, مسعود (جامعة الوادي - University of Eloued, 2023)
This research aims to study the impact of intellectual capital on total quality management in El Hadjar Steel Complex with the existence of job satisfaction as an intermediate variable. Data was collected by distributing a questionnaire to a non random sample of 83 employees in the bank. In order to test the study hypotheses, the Statistical Package for Social Science Program (SPSS V25) and AMOS V21 were used. The results showed that indirect significant effect between intellectual capital and total quality management in El Hadjar Steel Complex with the existent of job satisfaction as an intermediate variable.
job satisfaction as an intermediate variable between intellectual capital and total quality management: case El Hadjar Steel Complex
مقال
Keywords: الرأس المال الفكري ; الرضا الوظيفي ; إدارة الجودة الشاملة; intellectual capital; job satisfaction; total quality management.